Defining ‘Satisfactory Response’ to Therapy in Abdominal Tuberculosis: A Work in Progress - Sharma, Vishal; Singh, Harjeet; Mandavdhare, Harshal S. (Infectious Disorders - Drug Targets, 2020)
Abdominal tuberculosis is difficult to diagnose due to low sensitivity of microbiological tests and the low histological yield. Satisfactory response to therapy has long been used a criteria for the diagnosis of abdominal tuberculosis. However, the appropriate definitions of response to therapy in abdominal tuberculosis have remained unclear. Recent evidence suggests that mucosal healing of ulcers at the end of therapy or at two months (early mucosal response) is a helpful criteria of response to therapy. This also helps in exclusion of multidrug resistant tuberculosis and alternative diagnosis like Crohn’s disease. Further limited literature suggests the use of some biomarkers like C-reactive protein in the follow-up of patients with peritoneal or intestinal tuberculosis.
Keywords: cocoon